HUBUNGAN PROBLEM SOLVING APPRAISAL TERHADAP PENYESUAIAN DIRI NARAPIDANA ANAK DI LEMBAGA PEMASYARAKATAN KELAS II B RANGKASBITUNG - Siti Erma Maemunah; Amat Hidayat (Jurnal Anak Bangsa, 2022)
Prison is a place of punishment for criminals who violate criminal law. Prisons are places where people are locked up and restricted in various ways. Jail for this child is something that will make everything lose. children will lose their families, lose the opportunity to play with their peers, lose the opportunity to learn at school, lack of stimulation, and can make child prisoners experience psychological disorders. This problem will make it difficult for children to accept the reality when they are in prison. When entering prison, child prisoners must be able to adapt to the prison environment, both with the prison, even other child prisoners, rules and regulations, as well as habits carried out in prison. To adapt to these problems and situations, child prisoners need a Problem Solving Appraisal to support the resolution of the problems they face. The purpose of this study was to examine the relationship between Problem Solving Appraisal and adjustment to child prisoners. The method used in this research is the correlation method with a quantitative approach. The results showed that there was a relationship between Problem Solving Appraisal and adjustment to prisoners in Class II B Rangkasbitung Correctional Institution with a correlation level of +0.473. Based on the results of the study, it can be interpreted that child prisoners who believe themselves to be Effective Problem Solvers are able to adjust well in Class II B Rangkasbitung Penitentiary